Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages FOREWORD. Much consideration is being given at the present time to what may be called the ménage of hospitals and hospital feeding. The present report deals with the personnel required for the domestic side of hospital management and stresses the fact that it is essential that fully trained and qualified personnel should be employed in the best interest of both patients and staff. The report gives full details of the requirements and accommodation essential for the welfare of the domestic staff, a matter which has, in some cases, not received full consideration in the past. To those interested, this report makes a contribution to this important subject which is well worth studying. HORDER. 11th September, 1943. REPORT of the HOSPITAL SUB-COMMITTEE INTRODUCTION. The Institutional Management Association was founded in 1938 as a professional association for women who have trained in domestic subjects, and have taken up a career of domestic management in institutions or commerce. One of the principal objects of the Association is to improve and safeguard the position of qualified women holding responsible posts in institutional management and commercial catering. The Association also endeavours to increase the opportunities open to them. The Association has amongst its members a number of trained women employed in the domestic departments of hospitals, and it is as a result of evidence obtained from such members that this Report has been written. In February, 1942, in view of the fact that responsible bodies were already discussing post-war organisation in hospitals, the Executive Committee of the Institutional Management Association decided to appoint a Sub-Committee consisting of members experienced in hospital administration to consider the position of hospital caterers and housekeepers. The Sub-Committee was invited to make recommendations on their training and conditions of employment with a view to attracting women of high professional qualifications to this work, and thus securing the best possible service in the domestic sphere for those who are sick and for those who care for them. The Sub-Committee was unanimous in its findings. 1 292/842/2/104